2012
DOI: 10.3389/fpsyg.2012.00437
|View full text |Cite
|
Sign up to set email alerts
|

“Distracters” Do Not Always Distract: Visual Working Memory for Angry Faces is Enhanced by Incidental Emotional Words

Abstract: We are often required to filter out distraction in order to focus on a primary task during which working memory (WM) is engaged. Previous research has shown that negative versus neutral distracters presented during a visual WM maintenance period significantly impair memory for neutral information. However, the contents of WM are often also emotional in nature. The question we address here is how incidental information might impact upon visual WM when both this and the memory items contain emotional information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 51 publications
(70 reference statements)
0
14
2
Order By: Relevance
“…It is important to note that we do not claim here that angry face representations do not decay at all in WM, but that decay might be more gradual, or have less impact on the precision of representations in WM at the point of retrieval compared to happy face representations. The lack of an anger-enhancement effect when a 9 second maintenance interval was used in previous work (Jackson et al, 2012) indicates clearly that the benefit to WM afforded by anger is lost over longer periods of time. It would be interesting for future study to try to ascertain in more detail the time-course of decay for angry and happy faces and the impact on representational precision.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It is important to note that we do not claim here that angry face representations do not decay at all in WM, but that decay might be more gradual, or have less impact on the precision of representations in WM at the point of retrieval compared to happy face representations. The lack of an anger-enhancement effect when a 9 second maintenance interval was used in previous work (Jackson et al, 2012) indicates clearly that the benefit to WM afforded by anger is lost over longer periods of time. It would be interesting for future study to try to ascertain in more detail the time-course of decay for angry and happy faces and the impact on representational precision.…”
Section: Discussionmentioning
confidence: 91%
“…Recent work provides evidence that the valence of task-irrelevant intervening information can influence WM for emotional stimuli. Jackson, Linden, and Raymond (2012) found that when the WM maintenance period was protracted to 9 seconds, the angry versus happy benefit observable with a 1 second maintenance period (Jackson et al, 2009) was abolished. However, when a task-irrelevant emotional (positive or negative) word was presented during maintenance, WM for the identity of angry faces was boosted (relative to when a neutral or no word was presented), resulting in the re-instatement of the angerenhancement effect.…”
mentioning
confidence: 99%
“…In contrast, previously observed facilitatory effects of emotion may operate more rapidly, potentially increasing the precision with which emotional stimuli can be encoded (Jackson et al ., ). Consistent with this possibility, the size of the VWM advantage for angry faces is reduced when longer encoding times are allowed (Jackson et al ., ), and it is eliminated when a long retention interval is used (Jackson, Linden, & Raymond, ). A long retention interval may allow competitive or other interference effects to accumulate to a larger degree.…”
Section: Discussionmentioning
confidence: 99%
“…Presentation of emotional faces versus emotional words showed quantitatively different levels of interference in individuals induced to feel sad mood, with the verbal domain showing more attentional interference than face domain [26]. Incongruent emotional word distractors can also disproportionately bias recall of certain emotional faces, with increased recall for angry faces paired with emotional words (whether positive or negative) relative to angry faces paired with neutral or no words [27]. Finally, repetition effects that influence subsequent memory performance differ for face and word stimuli [28], with repetition seeming to influence memory for lexical stimuli more than face stimuli.…”
Section: Introductionmentioning
confidence: 99%